Letter: identifying coeliac disease among patients with bloating. Issue 8 (3rd October 2018) - Ellul, P.; Zammit, C.
Abstract : Linked Content This article is linked to Hujoel et al and Hujoel and Rubio‐Tapia papers. To view these articles visit https://doi.org/10.1111/apt.14625 and https://doi.org/10.1111/apt.14964 .